Development and validation of a competitive hybrid ELISA for Seriola lalandi Vitellogenin. (17th February 2020) - Sanchis, Pablo J.; Nocillado, Josephine; Cheetham, Norm; Miller, Adam; Powell, Daniel; Wang, Tianfang; Elizur, Abigail
Abstract: The main objective of this study was to develop an enzyme‐linked immunosorbent assay (ELISA) for Seriola lalandi vitellogenin (Vtg). Nucleotide sequences corresponding to VtgAa, VtgAb and VtgC were obtained from S. lalandi liver transcriptomic data. Two peptides (12 amino acids each) were synthesized according to the predicted conserved regions of VtgAa and VtgAb, and used to generate two polyclonal antibodies in rabbits: anti‐ S. lalandi VtgA and anti‐ S. lalandi VtgB. Plasma from male S. lalandi treated with 17β‐estradiol (E2 ) was fractionated to produce the Vtg standard and analysed through SDS‐PAGE and Western blot. LC‐MS/MS analysis showed that the fraction corresponding to the highest peak consisted mainly of VtgAa and VtgAb. Two homologous antibodies (anti‐ S. lalandi VtgA and anti‐ S. lalandi VtgB) and one heterologous antibody (anti‐ Mugil cephalus Vtg) were tested to develop the S. lalandi ELISA. While the antibodies against the Vtg peptides were not effectively recognizing the Vtg standard, parallelism was confirmed between the M. cephalus Vtg standard and the S. lalandi Vtg standard. The ELISA developed is highly specific (no cross‐reaction with other proteins present in plasma when samples were diluted over 1:20), precise (the inter‐assay coefficient of variation at 50% binding was 13%) and sensitive (19 ng/ml). The assay was validated by quantifying the plasma Vtg levels in females at the start of the reproductive season and in E2 ‐treated males.